Determinants of open space values in highly urbanized cities in the Philippines case study of Makati City - Canlas, Maria Teresita B.; Liwag, Carmelita R.R.U.; Lidasan, Hussein S.; Rye, Rabinder Dickton S. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
Makati City is a highly urbanized district in the country and its fast losing its urban open spaces to development. Open space is defined as any open piece is defined as any open piece of land that is undeveloped (has no building or other built structures) and is accessible to the public (US-EPA 2006). It is unoccupied space open to the sky (HLURB CLUP Guide Book 2014), which can include green space such as parks, community gardens, urban forest, cemeteries, playgrounds and the like. Open spaces serve as the respiratory system of the ever growing and urbanizing world. The lack of usable open spaces in urban areas impacts not only the environment but even has social and economic consequences. To determine the reasons why Makati is losing its usable open spaces, the objectives of the study were to : 1)locate major usable public open spaces in Makati City, 20identify factors that contributed to the decrease or increase of open space, and 3) identify strategies for the creation of usable public open spaces in the city. Documentary analysis and key informant interview (KII) were used for the qualitative analysis and a survey of 180 respondents representing the spectrum of population of Makati City, served in the quantitative analysis for this study. The framework assumed that the decrease or increase of usable public open spaces in Makati City is influenced by factors such as government policies, demand for open spaces, and value of properties. The results of the study showed that Makati City has twenty-eight (28) open spaces, which make up a land area of 746,963 square meters or 2,73 percent of the entire City. In the period 1981-1998, the open space area in Makati City increased but from 1998 to 2112, it decreased. This is ascribed to several local and national policies, which included the disposition of the Fort Bonifacio Area and the recent trend of high density development. As to the demand for open space, the results of the survey showed that almost all of the respondents considered open spaces in their neighborhood essential and were willing to pay an entrance fee for the maintenance of these open spaces. However, the demand is not being translated into the actual creation of open space because it is not effectively conveyed to the local government authorities. The results of the Key Informant Interview (KII)among land developers revealed that they are willing to develop and incorporate preens and open spaces into their projects as these add to the character and aesthetics of their building units and do attract a market. However, property owners prefer to develop land into urban uses other than open spaces due to the current trend of development and cost of land. They believe that the provision of usable public open spaces for the use of the community is primarily the responsibility of local government.Some recommendations in this study are for the City government of Makati to :Establish an independent body for parks,Formulate an open space master-plan based on the ecological network concept.Convert government buildings' rooftops into functional open space to be accessible to the public and encourage private developers to convert or allocate their rooftops as functional open space. Improve conditions of the existing parks and open spaces to incorporate facilities and amenities.
Thesis (M.A Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Open spaces -- Philippines -- Makati City; City planning -- Philippines -- Makati City; Parks -- Philippines -- Makati City; Urban policy -- Philippines -- Makati City